(3UMjM GdHNGQjs - (3GdHNGQj, GdLYaj, CHh YHO Gddg, eMeO Hf ESeGYjd Hf EHQGgje, J (B256(3g`s ((3YHO GdQMef Hf YHO GdSdGes)
(3ChdgG (B:s
(3GHf YHGS(B: (3SFd Yf eJYI GdfSGA (S0(3aQNU(S1 (3, abGd dg ehdi dg(B: (3EfeG Pdc aj GdMGd GdTOjO, haj GdfSGA bdI? Ch fMhg, abGd GHf YHGS(B: (S0(3fYe(S1 (3MOKfG Ydj, MOKfG SajGf, bGd YeQh, Yf GdMSf Hf eMeO, YfGHQs
(3BNQgG (B:s
(3HGH GdeSJhTeI ef cJGH GddHGS hBNQg (B: (3MOKfG eMeO Hf GdeKfi, KfG YHO GdQMef, Yf SajGf, Yf efUhQ, Yf EHQGgje, Yf YdbeI, Yf YHO Gddg (S0(3dYf Gddg GdhGTeGJ hGdeSJhTeGJ, hGdeJfeUGJ, hGdeJadLGJ ddMSf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 34s
(3eYLe GdeDdajf (B3 / 130s
(3cTa GdXfhf (B1 / 541s
(3TPQGJ GdPgH (B2 / 132s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs